Perancangan Sistem Informasi Posyandu Lasi Kec Canduang Kab Agam Sumbar Berbasis Web Android - Teri Mengkasrinal; Efmi Maiyana; Silvia Silvia (Ikatan Ahli Informatika Indonesia, 2018)
Posyandu is a place of health services for toddlers and mothers, along with other health services including: checking the health of children under five, weighing the weight, monitoring the nutritional status, giving vitamin A, giving immunization consultation health problems and other health services, the main strategy to reduce the prevalence Nutritional problems are increasing prevention activities through monitoring the growth of children in posyandu early. However, there are some problems faced by these two partners is the low level of public participation to bring children to the posyandu, this is caused by daily busyness and lack of information media, poor nutrition of under-fives, facilities and infrastructure is very minimal, not there is a medium of communication between participants and health workers and experts and still lacks health education. To overcome the above problems, a comprehensive and comprehensive study is needed. The approach used in this activity is Research and Development (RnD) 4D version (define, design, develop and dessiminate). This approach produces the final product is web and android apps. Expected with android web-based Information Technology that can be accessed anytime and anywhere useful for giving information about mother and child health, information about posyandu implementation, whether in the form of monthly weighing activity, giving vitamin A, immunization and storage of maternal and child health data in technology, making it easier for all parties to check whenever necessary, can be a forum / media communication and discussion, especially health issues between posyandu officers with the community